Pengaruh Rasio Keuangan Terhadap Efisiensi Perusahaan (The Effect of Financial Ratios on Company Efficiency) - Aura Bunga Devismara; Akhmad Hikmalshah Akbar; Reiza Aulia Larasati (Akutansi Bisnis & Manajemen ( ABM ), 2022)
The object of this research is a manufacturing company listedaon the Indonesia StockaExchange. The purpose ofathis study isato examine and analyze theaeffect of leveragea(DER), liquiditya(CR), and profitabilitya(ROA) on company efficiency (TATO). The number of samples used is a number of 20 manufacturing companies obtained using purposive sampling technique. This study design is a causality study design. The researchamethod used is a typeaof quantitative study that is descriptive and analyzed using multiple linear regression methods. The results of thisastudy indicate partially: 1) DER hasaa negative and significant effectaon TATO, 2) CR hasaa positive and insignificant effectaon TATO, 3) ROA has a positive andasignificant effect on TATO.